Comparison of SAW and TOPSIS Methods in Decision Support Systems for Contraceptive Selection - Susilo, Joko; Wahyuni, Elyza Gustri (International Journal Software Engineering and Computer Science (IJSECS), 2024)
Family Planning (FP) is a crucial initiative in enhancing the quality of life and health of mothers and children. However, selecting the appropriate contraceptive method remains a significant challenge for many couples of reproductive age. This study proposes the development of a web-based Decision Support System (DSS) that integrates the Simple Additive Weighting (SAW) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) at Zahra Harapan Bunda Clinic. The system aims to provide accurate recommendations for selecting contraceptive methods, record data, monitor users, and remind acceptors of consultation schedules. The results indicate that the SAW method is more consistent and aligns more closely with expert recommendations compared to TOPSIS, with a higher conformity percentage ranging from 66.25% to 92.5%. In contrast, TOPSIS showed a lower conformity percentage, ranging from 25.89% to 78.03%. These findings suggest that SAW more accurately reflects expert recommendations and is therefore considered more effective for selecting contraceptive methods. The study recommends the use of the SAW method for decision-making in contraceptive method selection and suggests further research to expand and validate this approach in a broader range of applications.